Evaluation of PTR-ToF-MS as a tool to track the behavior of hop-derived compounds during the fermentation of beer. (September 2018) - Richter, T.M.; Silcock, P.; Algarra, A.; Eyres, G.T.; Capozzi, V.; Bremer, P.J.; Biasioli, F.
Abstract: Hop-derived volatile organic compounds (VOCs) play an important role in the flavor and aroma of beer, despite making up a small percentage of the overall profile. To understand the changes happening during fermentation, proton transfer reaction-time of flight-mass spectrometry (PTR-ToF-MS) was applied for the first time in brewing science to directly measure the changes in hop-derived VOCs during the fermentation of four different worts containing one of two aroma hops in combination with one of two yeast biotypes. PTR-ToF-MS successfully detected and tracked mass-to-charge ratios ( m / z ) arising from interactions between the different yeast strains and the hop cultivars. Differences were observed in the dynamic VOC profiles between different beer treatments for m / z such as m/z 145.121 (ethyl hexanoate) and m/z 173.153 (isoamyl isovalerate or ethyl octanoate). The ability to monitor changes in VOCs during fermentation provides valuable information on the priority of production and transformation reactions by yeast. Graphical abstract: Unlabelled Image Highlights: PTR-ToF-MS was applied for the first time in brewing science. Three different dynamics were observed for VOC development during fermentation. PTR-ToF-MS demonstrated dynamic changes in hop-derived VOCs. VOC profiles indicate specific hop-yeast interactions with potential impact on aroma perception.